Commencement exercise special awardees, 3rd term SY 1993-1994 - De La Salle University, Manila (Animo Repository, 1994)
Ma. Teresa de Manuel (DALL), Flora Calleja (MAGC), Ma. Carmen Gaerlan (DERVED), Ma. Corazon Manalo, D.C., and Tita Joy Barredo-Velasco received their Academic Awards with High Distinction during the Commencement Exercises, Third Trimester SY 1993-1994.